2021
DOI: 10.1177/2333794x21991532
|View full text |Cite
|
Sign up to set email alerts
|

The Two-bag System for Intravenous Fluid Management of Children with Diabetic Ketoacidosis: Experience from a Community-Based Hospital

Abstract: Objectives: Intravenous fluid (IVF) administration using the two-bag system compared with the one-bag system in children with diabetic ketoacidosis (DKA) admitted between January 1, 2015 and December 31, 2016. Design: Retrospective cohort study. Setting: Community-based hospital. Results: A total of 109 patients were enrolled with a mean age of 13.24 years. The 2 groups had comparable demographics. Initial laboratory results were similar except for initial PH and Sodium. The two bag system had significantly le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The one‐bag system consists of an initial administration of a fluid with electrolytes and subsequent administration of dextrose to prevent hypoglycemia. This approach has been associated with slow response times and increased hospital costs 38,39 . Meanwhile, the two‐bag system consists of one bag with the fluid with electrolytes and another with a fixed dextrose concentration (e.g., 10% or 12.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The one‐bag system consists of an initial administration of a fluid with electrolytes and subsequent administration of dextrose to prevent hypoglycemia. This approach has been associated with slow response times and increased hospital costs 38,39 . Meanwhile, the two‐bag system consists of one bag with the fluid with electrolytes and another with a fixed dextrose concentration (e.g., 10% or 12.5%).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been associated with slow response times and increased hospital costs. 38,39 Meanwhile, the two-bag system consists of one bag with the fluid with electrolytes and another with a fixed dextrose concentration (e.g., 10% or 12.5%). By adjusting the administration rates of each bag individually, we provide different concentrations of glucose while keeping a constant final fluid delivery.…”
Section: Administration Systemmentioning
confidence: 99%
“…This accomplishment occurred through use of standardized DKA guidelines built on a two-bag fluid system, standardization of hand-offs, inclusion and education of all stakeholders, and explicit EMR orders to support clinical practice. While previous retrospective studies evaluating use of standardized management of DKA with or without two bag fluid system indicate the potential for decreased cost, 4,13,14 more rapid DKA resolution, 5,15 and/or decreased rates of hypoglycemia 5,7,8 ; to our knowledge, our study is the first to demonstrate how various tenets of quality improvement science can be prospectively paired with the implementation of standardized DKA guidelines based on a two-bag fluid system with the primary objective to decrease the rate of low BGs in pediatric patients with DKA.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing two-bag to one-bag fluid management, retrospective studies have demonstrated a variety of potential benefits and harms [19][20][21][22]. Possible benefits include faster resolution of acidosis, lower resource utilization, and lower hypoglycaemia and hypokalaemia.…”
Section: Recent Evidencementioning
confidence: 99%